A: \( y = e^{2x} - {e}^{ - 2x} + \cos x \)
B: \( y = {\log _2} { { 1 + x} \over {1 -x}} \)
C: \( y = 3{x^4} - {x^3} \)
D: \( y = { { {e^x} + {e^{ - x}}} \over 2} \)
举一反三
- 下列函数为偶函数的是( )。 A: \( y = {2{e}^{2x}} - {2{e}^{ - 2x}} + \sin x \) B: \( y = {\log _a} { { 1 - x} \over {1 + x}} \) C: \( y = { { {e^x} + {e^{ - x}}} \over 2} \) D: \( y = 3{x^2} - {x^3} \)
- 函数\(y = \ln \left( {1 + {x^2}} \right)\)的导数为( ). A: \( { { 2x} \over {1 + {x^2}}}\) B: \( - { { 2x} \over {1 + {x^2}}}\) C: \( { { 2x} \over {1 - {x^2}}}\) D: \( - { { 2x} \over {1 - {x^2}}}\)
- 下列函数中,( )不是方程\( xy' + y - x^2 = 0 \)的解。 A: \( y = { { {x^2}} \over 3} + {1 \over x} \) B: \( y = { { {x^2}} \over 3} \) C: \( y = { { {x^2}} \over 3} + 2 \) D: \( y = { { {x^2}} \over 3} - {1 \over x} \)
- 设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}({x^2}y + {y^3} + 2x)\) B: \({e^{xy}}({x}y^2 + {y^3} + 2x)\) C: \({e^{xy}}({x}y + {y^3} + 2x)\) D: \({e^{xy}}({x^2}y + {y^2} + 2x)\)
- 函数\(y = {x^2} - \ln x\)的导数为( ). A: \(2x - {1 \over x}\) B: \(2x + {1 \over x}\) C: \( - 2x + {1 \over x}\) D: \( - 2x - {1 \over x}\)
内容
- 0
已知\( y = \ln (1 + {x^2}) \),则\( y' \)为( ). A: \( { { 2x} \over {1 + {x^2}}} \) B: \( {x \over {1 + {x^2}}} \) C: \( {1 \over {1 + {x^2}}} \) D: \( { { {x^2}} \over {1 + {x^2}}} \)
- 1
设\(z = {e^ { { y \over x}}} + {x^y} + {y^x}\),则\({z_x} = \) A: \({1 \over x}{e^ { { y \over x}}} + {x^y}\ln x + x{y^{x - 1}}\) B: \(- {y \over { { x^2}}}{e^ { { y \over x}}} + {x^y}\ln x + x{y^{x - 1}}\) C: \({e^ { { y \over x}}} + y{x^{y - 1}} + {y^x}\ln y\) D: \( - {y \over { { x^2}}}{e^ { { y \over x}}} + y{x^{y - 1}} + {y^x}\ln y\)
- 2
下列不等式正确的是( ) A: \( { { {e^x} + {e^y}} \over 2} < {e^ { { {x + y} \over 2}}}\quad (x \ne y)\) B: \((x + y){e^{x + y}} < x{e^{2x}} + y{e^{2y}}\quad (x > 0,y > 0,x \ne y)\) C: \( { { {x^n} + {y^n}} \over 2} < {( { { x + y} \over 2})^n}\quad (x > 0,y > 0,x \ne y,n > 1)\) D: \(x\ln x + y\ln y < (x + y)ln { { x + y} \over 2}\quad (x > 0,y > 0,x \ne y)\)
- 3
求函数$y = {{1 + \root 3 \of {{x^2}} - \sqrt {2x} } \over {\sqrt x }}$的导数$y' = $( ) A: $ {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ B: $ - {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ C: ${1 \over 2}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$ D: ${1 \over 3}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$
- 4
函数\(y = {e^{ - {x^2}}}\)的导数为( ). A: \( - 2x{e^{ - {x^2}}}\) B: \(2x{e^{ - {x^2}}}\) C: \( - 2x{e^ { { x^2}}}\) D: \(2x{e^ { { x^2}}}\)